2023
DOI: 10.3389/fneur.2023.1104759
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation in Parkinson's disease—A randomized repeat-dose, placebo-controlled clinical pilot study

Abstract: Background and purposeThe intestinal microbiome plays a primary role in the pathogenesis of neurodegenerative disorders and may provide an opportunity for disease modification. We performed a pilot clinical study looking at the safety of fecal microbiota transplantation (FMT), its effect on the microbiome, and improvement of symptoms in Parkinson's disease.MethodsThis was a randomized, double-blind placebo-controlled pilot study, wherein orally administered lyophilized FMT product or matching placebo was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 68 publications
1
31
1
Order By: Relevance
“…The value of the biomarker in this case is to avoid supplementation that is counter indicated. FMT is showing promise for PD 28 , but it carries risks concerning safety and compatibility of donor sample with host environment. Using biomarkers, unnecessary FMT can be avoided, sparing the patients who do not have a dysbiotic microbiome and those whose only problem is low fiber-degraders.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the biomarker in this case is to avoid supplementation that is counter indicated. FMT is showing promise for PD 28 , but it carries risks concerning safety and compatibility of donor sample with host environment. Using biomarkers, unnecessary FMT can be avoided, sparing the patients who do not have a dysbiotic microbiome and those whose only problem is low fiber-degraders.…”
Section: Discussionmentioning
confidence: 99%
“…FMT has been shown to be beneficial in patients with Clostridium difficile infections and irritable bowel syndrome (IBS) where there is dysbiosis ( Barichella et al, 2016 ). Presently, there are multiple ongoing clinical trials investigating the effects of FMT on PD symptoms including constipation, motor symptoms, and restoration of gut homeostasis ( Xue et al, 2020 ; Kuai et al, 2021 ; Metta et al, 2021 ; Segal et al, 2021 ; DuPont et al, 2023 ), NCT03808389, NCT04854291, NCT05204641, NCT03671785 and it is possible that utilization of FMT in combination with DATs could improve PD progression and symptomology.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Recently, a double-blind, placebo-controlled pilot study, using orally administered, lyophilized FMT twice weekly for 12 weeks, reported improvements in subjective motor and non-motor symptoms, gut transit, intestinal motility, and constipation in PD patients. Moreover, proportions of selective families within the phylum Firmicutes significantly increased after FMT, while the proportion of Proteobacteria was significantly reduced [329].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 94%